Peran Independensi, Pengalaman Kerja dan Etika Audit dalam Meningkatkan Kualitas Audit Internal Pemerintah - Mamulati, Irman; Muhammad, Irsad (Jurnal Ilmiah Akuntansi Peradaban, 2025)
The quality of internal government audits in Indonesia has come under public scrutiny due to numerous corruption cases in various regions. Even the audit opinion issued by the Supreme Audit Agency (BPK RI) does not guarantee that a region is free from corruption. This is due to weak independence, work experience, and audit ethics, which are often overlooked by government auditors. This study aims to analyze the influence of auditor independence, work experience, and ethics on the quality of internal audits in the North Maluku Provincial Government. The data analysis method used was multiple linear regression analysis. A total of 35 auditors served as the sample. The analysis tool used was SPSS 28, which processed the data. The results showed that auditor independence, work experience, and ethics influenced audit quality.